“Neonatal Hemolytic Anemia due to Glucose-6-Phosphate Dehydrogenase Deficiency: A Case Report - Nadia Atika; Nazardi Oyong (Universitas Malahayati Lampung, 2026)
ABSTRACT Glucose-6-phosphate dehydrogenase (G6PD) deficiency is one of the most common hereditary enzymatic disorders affecting red blood cells worldwide and is a significant cause of neonatal hyperbilirubinemia and hemolytic anemia. Clinical manifestations in neonates are variable and may present atypically, leading to delayed diagnosis and management. We report a case of a term male neonate delivered via cesarean section who developed progressive respiratory distress shortly after birth. The infant had Apgar scores of 7 and 8 at 1 and 5 minutes, respectively, and required continuous positive airway pressure (CPAP) due to worsening respiratory distress. Laboratory evaluation revealed metabolic acidosis, electrolyte imbalance, anemia (hemoglobin 11.4 g/dL), and coagulopathy. Subsequent findings showed fluctuating hemoglobin levels, suggesting ongoing hemolysis. Screening for G6PD deficiency demonstrated reduced enzyme activity (1.2 U/g Hb), which was later confirmed by quantitative assay (2.8 U/g Hb; reference 10.0–14.2), consistent with G6PD deficiency. The patient was diagnosed with neonatal pneumonia and hemolytic anemia secondary to G6PD deficiency. Clinical condition improved with supportive management, including respiratory support and antibiotic therapy. This case represents an atypical presentation of G6PD deficiency, where respiratory distress and systemic involvement preceded classical features such as jaundice. The patient’s enzyme activity corresponds to Class III (moderate deficiency) based on WHO classification, in which hemolysis is often triggered by oxidative stress, particularly infection. Neonatal pneumonia likely acted as the precipitating factor in this case. The variability in clinical presentation highlights the diagnostic challenges of G6PD deficiency in neonates. G6PD deficiency should be considered in neonates with unexplained anemia or clinical deterioration, even in the absence of overt jaundice. Early recognition and appropriate management are essential to prevent severe complications, including acute hemolysis and bilirubin-induced neurologic dysfunction. Keywords: Neonatal, Hemolytic Anemia.